SISTEM VERIFIKASI LEGALITAS KAYU DAN PERBANDINGANNYA DENGAN SERTIFIKASI SUKARELA PADA LEVEL INDUSTRI - Magdalena Gultom; Satria Astana; Rachman Effendy; Andri Setiadi Kurniawan (Jurnal Analisis Kebijakan Kehutanan, 2014)
Indonesia has established the timber legality assurance system (SVLK) to ensure legal logging and timber trade. In January 2013, most of the export of wood products have to fulfil SVLK's requirements. Considering the improvement of SVLK implementation, the objectives of this study are to understand  related regulations and involved stakeholders in SVLK implementaion, and to compare profile and cost of SVLK with voluntary certifications at industrial level. The methods used to collect data included interviews of related  stakeholders (government officials, NGOs, auditors), focus group discussions and meetings. The data was analyzed descriptively and qualitatively. The study results showed that SVLK implementation need to be refined in terms of rules synchronization, coordination, socialization, financial support and training for small scale industries as well as assessment criteria for the industries having diverse sources of raw materials. The revised standard cost  for  SVLK certification has been relatively similar to those of voluntary certifications but there is a concern for illegal fees on the SVLK  implementation.